Old age home mobile application - Tan, Teck Wei (2024)
The development of information and communication technologies have accelerated the pace of people’s life. Thus, many young people are spending a lot of time to struggle for business. One case to take specifically into account is older people. Since offering a good quality elderly healthcare is an enduring and complicated process, there is a significant need to develop innovative solutions to benefit the society as large. The mobile application is not always applied for them and meet their needs. Therefore, this project is concentrated on mobile application design for academic purpose. It mainly focuses on the field of user-friendly old age home mobile application that provide the essential information for the family members about the plan, activity, meal, and services offered for the elder. The mobile application is expected to help elder in using mobile application as well as family members to contact with their elder. From the perspective of design, the project is emphasis on system that enable users to log-in, check daily activities, record medical record, communicating with others, providing relevant information about the elder to the family members and etc. There are several parts for the mobile application which included Medical Record, Chat and Message, Pill Reminder, Emergency Call, Remote Monitoring and etc. This project is making use of use case diagrams to describe the system processes and class diagram to illustrate the flow between the actions in an activity. Since mobile programming and real-time Firebase is well suited for the mobile application development, therefore it is used in this project. Even though there have numerous mobile application that focused on the elderly healthcare, however; there are still lack of some functionalities that able to improve the quality of life for the elder. By studying this project, it presents the mobile application functionalities and emerge the strategies that can satisfy the needs of the elder and improve their quality of life.